2021
DOI: 10.3926/jotse.1175
|View full text |Cite
|
Sign up to set email alerts
|

The effect of digital eco-learning in student worksheet flipbook to environmental project literacy and pedagogic competency

Abstract: The study aimed to determine 1) the effect of digital eco learning in student worksheet flipbooks on environmental literacy projects, and 2) the effect of digital eco learning in student worksheet flipbooks on student ecological competence. The research is a quasi-experimental study using a Pretest-Posttest Non-equivalent Control Group. The research subjects were students in the Environmental Geography course semester 6 of 2020, divided into the experimental and control groups. The research was conducted at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 27 publications
(38 reference statements)
1
16
0
5
Order By: Relevance
“…Electronic based instructional material requires in increasing students` learning interest (Anwar, et al, 2019). Electronic worksheet facilitated student communicating with teachers due to online learning (Sumarni, et al, 2021). Further research found that the augmented reality (AR) worksheets improved learning outcomes more effectively than paper worksheets and also performed better interaction among learner, mobile device, and physical context (Zhang, 2020).…”
Section: Electronic Workheet In E-learningmentioning
confidence: 99%
“…Electronic based instructional material requires in increasing students` learning interest (Anwar, et al, 2019). Electronic worksheet facilitated student communicating with teachers due to online learning (Sumarni, et al, 2021). Further research found that the augmented reality (AR) worksheets improved learning outcomes more effectively than paper worksheets and also performed better interaction among learner, mobile device, and physical context (Zhang, 2020).…”
Section: Electronic Workheet In E-learningmentioning
confidence: 99%
“…Pengumpulan tugas dan penilaian hasil pembelajaran bahkan sejak 1996 telah diterapkan melalui File Transfer Protocol (FTP) dan berbentuk HTML (Dumont, 1996). Pembelajaran online dapat mempermudah pengumpulan data proyek melalui file digital (Sumarmi et al, 2021).…”
Section: Tantangan Epistemologi Geografiunclassified
“…With method this , frequency study child could increase so that mastery child to presented material Becomes more great (Irham et al, 2017;Harwati & Rokhmat, 2021). From the description above , can concluded that method sheet work student is method effective study on the side practice student for think fast and skilled in count , also embed as early as possible will importance dominate calculation base as capital for understand science concepts (Sumarmi et al, 2021).…”
Section: Introductionmentioning
confidence: 97%